(untitled) (Jurnal Lemhannas RI, 2024)
Purpose: This study aims to explore the factors behind Ukraine’s rejection of the peace proposal suggested by Indonesian Defence Minister Prabowo Subianto at a global defence ministers’ forum in June 2023. The objective is to understand Ukraine’s concerns and to propose potential adjustments that could make future peace proposals more acceptable to both Ukraine and Russia, contributing to a more balanced conflict resolution. Study Design/Methodology/Approach: The research employs an explanatory qualitative approach, analyzing information from documents, journals, books, and other relevant scientific literature. The study focuses on Ukraine’s response to Subianto’s peace proposal and examines the geopolitical and sovereignty-related reasons for its rejection. Findings: The findings reveal that Ukraine’s rejection stemmed from concerns that the proposal favored Russia and compromised Ukrainian sovereignty. The study concludes that Indonesia’s peace proposal would require significant adjustments to address these sovereignty issues, ensuring a fair and balanced approach that would not impose undue burdens on Ukraine. Originality/Value: This study contributes to the discourse on peace-building and conflict resolution by offering insights into the complexities of international mediation. It highlights the importance of fair and balanced proposals in resolving geopolitical conflicts and provides recommendations for improving future initiatives to mediate between Russia and Ukraine effectively. The study offers valuable perspectives for policymakers and international mediators seeking to facilitate sustainable peace agreements